2006
DOI: 10.1063/1.2396763
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Ni nanoparticles as the origin of ferromagnetism in Ni implanted ZnO crystals

Abstract: We report the structural and magnetic properties of ZnO single crystals implanted at 623 K with up to 10 at. % of Ni. As revealed by X-ray diffraction, crystalline fcc-Ni nanoparticles were formed inside ZnO. The magnetic behavior (magnetization with field reversal and with different temperature protocol) of all samples is well explained by a magnetic Ni-nanoparticle system. Although the formation of Ni:ZnO based diluted magnetic semiconductor cannot be ruled out, the major contribution to the magnetic propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…In some cases, the observed room temperature ferromagnetism (RTFM) was claimed to be carrier mediated [19,23] or occurring due to defects [22] or oxygen vacancies [24][25][26]. Still in a few other cases, Ni clusters were responsible for observed RTFM [27][28][29]. It is also reported that homogeneous incorporation of Ni in ZnO results in paramagnetic samples, whereas the imperfectly doped samples lead to ferromagnetism [30].…”
Section: Introductionmentioning
confidence: 95%
“…In some cases, the observed room temperature ferromagnetism (RTFM) was claimed to be carrier mediated [19,23] or occurring due to defects [22] or oxygen vacancies [24][25][26]. Still in a few other cases, Ni clusters were responsible for observed RTFM [27][28][29]. It is also reported that homogeneous incorporation of Ni in ZnO results in paramagnetic samples, whereas the imperfectly doped samples lead to ferromagnetism [30].…”
Section: Introductionmentioning
confidence: 95%
“…These kinds of materials are fabricated by doping oxide semiconductors, such as ZnO, TiO 2 , SnO 2 , and In 2 O 3 , with transition metals. Many groups have reported the observation of ferromagnetism in transition-metal-doped rutile and anatase TiO 2 [1][2][3][4]. However, the origin for the measured ferromagnetism is questionable.…”
mentioning
confidence: 91%
“…Temperature dependent magnetization was measured after zero field cooling and field cooling (ZFC/FC) [31]. Note that SQUID magnetometry is an integral method, which measures the total magnetic response from the sample, including substrate and possible contaminations from previous processing [43,44].…”
Section: Experimental Methodsmentioning
confidence: 99%